Influence of hydrothermal venting on water column properties in the crater of the Kolumbo submarine volcano, Santorini volcanic field (Greece) - Christopoulou, M. E.; Mertzimekis, T. J.; Nomikou, P.; Papanikolaou, D.; Carey, S.; Mandalakis, M. (Geo-Marine Letters, 2015)
The Kolumbo submarine volcano, located 7 km northeast of the island of Santorini, is part of Santorini’s volcanic complex in the south Aegean Sea, Greece. Kolumbo’s last eruption was in 1650 AD. However, a unique and active hydrothermal vent field has been revealed in the northern part of its crater floor during an oceanographic survey by remotely operated vehicles (ROVs) in 2006. In the present study, conductivity-temperature-depth (CTD) data collected by ROV Hercules during three oceanographic surveys onboard E/V Nautilus in 2010 and 2011 have served to investigate the distribution of physicochemical properties in the water column, as well as their behavior directly over the hydrothermal field. Additional CTD measurements were carried out in volcanic cone 3 (VC3) along the same volcanic chain but located 3 km northeast of Kolumbo where no hydrothermal activity has been detected to date. CTD profiles exhibit pronounced anomalies directly above the active vents on Kolumbo’s crater floor. In contrast, VC3 data revealed no such anomalies, essentially resembling open-sea (background) conditions. Steep increases of temperature (e.g., from 16 to 19 °C) and conductivity near the maximum depth (504 m) inside Kolumbo’s cone show marked spatiotemporal correlation. Vertical distributions of CTD signatures suggest a strong connection to Kolumbo’s morphology, with four distinct zones identified (open sea, turbid flow, invariable state, hydrothermal vent field). Additionally, overlaying the near-seafloor temperature measurements on an X–Y coordinate grid generates a detailed 2D distribution of the hydrothermal vent field and clarifies the influence of fluid discharges in its formation.